In vitro characterization and genetic diversity of Bordetella avium field strains. Issue 1 (2nd January 2020) - Knab, Rebecca; Petersen, Henning; Lin, Hsuen-Ju; Meixner, Martin; Rautenschlein, Silke; Jung, Arne
ABSTRACT: Bordetella avium (BA) is a respiratory pathogen of particular importance for turkeys. Specific adherence and damage to the respiratory epithelia are crucial steps of the pathogenesis, but knowledge about the mechanisms and the variety of virulence in field strains is limited. We analysed 17 BA field strains regarding their in vitro virulence-associated properties in tracheal organ cultures (TOC) of turkey embryos, and their genetic diversity. The TOC adherence assay indicated that BA field strains differ considerably in their ability to adhere to the tracheal mucosa, while the TOC ciliostasis assay illustrated a high degree of diversity in ciliostatic effects. These two virulence-associated properties were associated with each other in the investigated strains. Three of the investigated strains displayed significantly ( P  > 0.05) lower in vitro virulence in comparison to other strains. Genetic diversity of BA strains was analysed by core genome multilocus sequence typing (cgMLST). We applied a cgMLST scheme comprising 2667 targets of the reference genome (77.3% of complete genome, BA strain 197N). The results showed a broad genetic diversity in BA field strains but did not demonstrate a correlation between sequence type and virulence-associated properties. The cgMLST analysis revealed that strains with less marked virulence-associated properties had a variety of mutations in the putative filamentous haemagglutinin gene. Likewise, amino acid sequence alignment indicated variations in the protein. The results from our study showed that both adherence and ciliostasis assay can be used for virulence characterization of BA. Variations in the filamentous haemagglutinin protein may be responsible for reduced virulence of BA field strains.